2021
DOI: 10.1007/s43832-021-00008-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey of irrigation water and soil quality that likely impacts paddy rice yields in Kilimanjaro, Tanzania

Abstract: In this study, the impacts of irrigation water quality and soil characteristics on paddy rice yields were investigated. Standard spectroscopy and spectrometry methods were used to analyze irrigation water and irrigated soil samples. The irrigation water had sodium adsorption ratio (SAR) values ranging from 0 to 3. The corresponding electrical conductivity (EC) values were between 0.2 and 0.7 dS/m and accounted for 14% of all samples—posing slight to moderate infiltration problem. Neither Na+ nor Cl− levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…have been found in irrigation water for paddy rice, associated with intensive use of synthetic fertilisers(Mpanda et al, 2021). In the Kikafu River, further south of the study area and downstream of Moshi town, high levels of EC, TDS and NO 3 -N were found, exceeding the guidelines for irrigation use.…”
mentioning
confidence: 81%
“…have been found in irrigation water for paddy rice, associated with intensive use of synthetic fertilisers(Mpanda et al, 2021). In the Kikafu River, further south of the study area and downstream of Moshi town, high levels of EC, TDS and NO 3 -N were found, exceeding the guidelines for irrigation use.…”
mentioning
confidence: 81%